136k views
3 votes
Im so confused please help​

Im so confused please help​-example-1
User Jadranka
by
5.8k points

2 Answers

5 votes

Answer:

9

Explanation:

They give you the equation:

2x+3

And they give you the (x):

x=3

So you simply replace (x) with 3

2x+3

2(3)+3

now solve

2•3= 6

6+3 = 9

9 is your answer.

Hope this helps! If you have any questions on how I got my answer feel free to ask. Stay safe!

User Srinivas Damam
by
5.6k points
2 votes

Answer:

9

Explanation:

It's just telling you that the value of x is 3, so in the equation,

you replace x with 3,

2(3) + 3,

2 x 3 = 6,

6+ 3 = 9

User Tushar Patel
by
5.4k points